2022
DOI: 10.1101/2022.05.04.490646
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AA-amyloidosis in cats (Felis catus) housed in shelters

Abstract: Systemic AA-amyloidosis is a protein-misfolding disease that is characterized by fibril deposition of serum amyloid-A protein (SAA) in several organs in humans and many animal species. Fibril deposits originate from abnormally high serum levels of SAA during chronic inflammation. In domestic short-hair cats, AA-amyloidosis has only been anecdotally reported and is considered a rare disease. Here we report that an astonishing 57-73% of early deceased short-hair cats kept in three independent shelters suffer fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…Full details were described previously 47 . In brief, organs were collected within 5 h from death, fixed in 10% formalin, and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Full details were described previously 47 . In brief, organs were collected within 5 h from death, fixed in 10% formalin, and embedded in paraffin.…”
Section: Methodsmentioning
confidence: 99%
“…A prion-like spread of AA amyloidosis was also inferred from studies in which parenteral administered amyloid accelerated deposition in inflamed animals 2,45,46 . Our recent study has revealed a prevalence of 57-73% among 80 domestic short hair (DSH) cats kept in shelters 47 , in stark contrast to a very low prevalence (1-2 %) in client-owned cats 4851 .…”
Section: Introductionmentioning
confidence: 97%
“…Importantly, SAA has been suggested as prion candidate, based on extreme disease prevalence in captive cheetah and experimentally accelerated AA amyloidosis in chronically inflamed animals after intravenous injection or oral administration of amyloid 2,48,50,51 . Our recent study has revealed a prevalence of 57-73% among 80 domestic short hair (DSH) cats kept in shelters 52 , in stark contrast to a very low prevalence (1-2%) in clientowned cats 53,54 . AA amyloid deposits were found in the kidney, liver, spleen, and even the heart 52 .…”
mentioning
confidence: 97%
“…Our recent study has revealed a prevalence of 57-73% among 80 domestic short hair (DSH) cats kept in shelters 52 , in stark contrast to a very low prevalence (1-2%) in clientowned cats 53,54 . AA amyloid deposits were found in the kidney, liver, spleen, and even the heart 52 . SAA was present in cat bile, indicating a potential fecal-oral transmission route, as reported for captive cheetah 39,52 .…”
mentioning
confidence: 97%
See 1 more Smart Citation